Disparitas Implementasi Sop Anti Anarkis Satuan Brimob Dengan Pelaksanaan Undang-Undang Nomor 9 Tahun 1998 Dalam Penanganan Unjuk Rasa Di Indonesia - Dinda Charelina Tahir Saputri (Indonesian Journal Publisher, 2026)
This study aims to analyze the legal framework governing the handling of public demonstrations in Indonesia and to examine the legal accountability of the Indonesian National Police Mobile Brigade Corps (Brimob) when actions undertaken during crowd control violate the Anti-Anarchist Standard Operating Procedure (SOP) and statutory regulations. The study employs a normative juridical approach through the examination of primary, secondary, and tertiary legal materials, including the 1945 Constitution, Law No. 9 of 1998 concerning Freedom of Expression in Public, Law No. 2 of 2002 concerning the Indonesian National Police, and internal police regulations related to demonstration management. Data were analyzed qualitatively using statutory and conceptual approaches. The findings indicate that Indonesian legal provisions emphasize the protection of citizens’ constitutional rights to express opinions while simultaneously mandating the maintenance of public order and security. Violations of operational procedures by Brimob personnel may result in administrative sanctions, criminal liability, and state responsibility for human rights violations and compensation claims. The study concludes that strengthening accountability mechanisms, supervision, and procedural compliance is essential to ensure that demonstration management remains proportional, lawful, and respectful of human rights principles.